Pemaknaan Term Qatlun dalam Ayat-Ayat Hubungan Manusia: Pendekatan Semantik Toshihiko Izutsu - Joni Saputra; Syefriyeni; Lukman Nul Hakim (Universitas Islam Negeri Kiai Ageng Muhammad Besari Ponorogo Indonesia, 2025)
This study discusses the semantic interpretation of the Qur'an in the context of modern understanding. The semantic approach is used to reveal the meaning of words and concepts in the Qur'an in more depth, by considering linguistic, historical, and social aspects. This study aims to show how semantic understanding can bridge the sacred text with the development of science, culture, and contemporary challenges. The method used in this study is qualitative analysis with the maudhu'i (thematic) interpretation approach and historical semantics. The results of the study show that semantic interpretation allows for a more contextual meaning of the verses of the Qur'an, so that it is relevant to modern life. In addition, this approach can overcome the bias of textualist understanding and provide new insights into the study of interpretation. Thus, this study contributes to enriching a more dynamic and inclusive understanding of the Qur'an, as well as encouraging dialogue between Islamic traditions and contemporary intellectual developments.